Curbing Key Digestive Enzymes by Three Plant Extracts for Sustainable Management of Postprandial Hyperglycemia - Sarker, Parth; Sani, Deedarul H.; Miah, Md. Faruque; Alam, Md. Jahangir (Letters in Drug Design & Discovery, 2024)
Background: Diabetes mellitus is a chronic metabolic condition marked by persistently elevated blood sugar levels. Key digestive enzymes viz. α-amylase and α-glucosidase, hydrolyze consumed carbohydrates into glucose which raises the postprandial blood glucose level in a diabetic patient. So, the development of α-amylase and α-glucosidase inhibitors procured from medicinal plants to retard starch digestion is an alternative approach for controlling type 2 diabetes mellitus. Objective: The current study aimed to evaluate the inhibitory potentials of the key digestive enzymes viz. α-amylase and α-glucosidase by the extracts of three medicinal plants; red dragon fruit (Hylocereus polyrhizus) pulp and peel, bamboo (Bambusa vulgaris) shoot, turnip (Brassica rapa L.) shoot and leaf by performing α-amylase and α-glucosidase inhibition assays in vitro. Methods: Inhibition of α-amylase activity was conducted using 3,5-dinitrosalicylic acid method, and 4- Nitrophenyl-α-D-glucopyranoside was used as a substrate to perform α-glucosidase inhibition assay in vitro. Results: Among all the selected sample extracts, red dragon fruit pulp expressed the highest percentage of α-amylase inhibition (59.73 ± 4.33%) at the concentration of 1000 μg/mL which is comparable to standard antidiabetic drug Acarbose (70.59 ± 2.64%), whereas the lowest inhibition was observed in turnip shoot extract (42.48 ± 2.10%) at the same concentration. In terms of α-glucosidase inhibition activity, again, red dragon fruit pulp extract demonstrated the maximum inhibition rate (56.42 ± 2.38%) at 1000 μg/mL concentration. This is respectable in comparison to the reference Acarbose (66.45 ± 1.78%). In contrast, turnip shoot extracts displayed the lowest α-glucosidase inhibition activity (38.27 ± 2.21%) at the same concentration. Conclusion: The current study demonstrated that the red dragon fruit pulp extract possesses substantial antihyperglycemic activity (α-amylase inhibition: 59.73 ± 4.33%, α-glucosidase inhibition: 56.42 ± 2.38%) in vitro, which could be a putative nutraceutical to manage postprandial hyperglycemia.
Keywords: antidiabetic activity